Use of the new World Health Organization child growth standards to describe longitudinal growth of breasfed rural Bangladeshi infants and young children - Saha, Kuntal K.; Frongillo, Edward A.; Alam, Dewan S.; Arifeen, Shams E.; Persson, Lars; Rasmussen, Kathleen M. (SAGE Publications, 2009)
Although the National Center for Health Statistics (NCHS) reference has been widely used, in 2006 the World Health Organization (WHO) released new standards for assessing growth of infants and children worldwide.To assess and compare the growth of breastfed rural Bangladeshi infants and young children based on the new WHO child growth standards and the NCHS reference.We followed 1,343 children in the Maternal and Infant Nutrition Intervention in Matlab (MINIMat) study from birth to 24 months of age. Weights and lengths of the children were measured monthly during infancy and quarterly in the second year of life. Anthropometric indices were calculated using both WHO standards and the NCHS reference. The growth pattern and estimates of undernutrition based on the WHO standards and the NCHS reference were compared.The mean birthweight was 2,697 ± 401 g, with 30% weighing < 2,500 g. The growth pattern of the MINIMat children more closely tracked the WHO standards than it did the NCHS reference. The rates of stunting based on the WHO standards were higher than the rates based on the NCHS reference throughout the first 24 months. The rates of underweight and wasting based on the WHO standards were significantly different from those based on the NCHS reference.This comparison confirms that use of the NCHS reference misidentifies undernutrition and the timing of growth faltering in infants and young children, which was a key rationale for constructing the new WHO standards. The new WHO child growth standards provide a benchmark for assessing the growth of breastfed infants and children.